The pancreas unmanned ground vehicle - Weinhold, Benjamin (Kansas State University, 2023)
Global agricultural output must increase by 25 to 70% by 2050 to feed the world. The development of more resilient, higher yield crops using genotype to phenotype prediction is one promising method to achieve this growth. Progress in genotype to phenotype models has been constrained by the quantity of hand measurements necessary to accurately describe phenotype characteristics. The Pancreas unmanned ground vehicle was developed to fill this gap in capability. The Pancreas is a four-wheeled unmanned vehicle which carries an electromagnetic inductance sensor to gather soil moisture data throughout the day. This sensor offers a reduction in the time required and an increase in the quantity of measurements taken over the typical soil core methods of measurement. The initial Pancreas prototypes were developed by Dr. Daniel Flippo and master’s student Calvin Dahms. The author made alterations to these designs to reflect a change in operational requirements after the testing results of these prototypes. Broadly, the platform was made more robust, a path following algorithm and new control system were implemented, and a new power budget was developed. Though these changes represent necessary improvements, the platform needs more work and testing to effectively perform its role. Increased power use, sensor accuracy, obstacle detection and avoidance, and durability remain problems to address in future work.
Keywords: Autonomous agricultural vehicle